Effects of catecholamines on volemic replacement with saline solution and the impact on heart rate variability in rabbits subjected to hemorrhage. A study by spectral analysis - Moraes, José Mariano Soares De; Vane, Matheus Fachini; Rodrigues, Denise De Fátima; Mostarda, Cristiano Teixeira; Moraes, Thiago Soares Mendes Moreira De; Vane, Lucas Fachini; Ganem, Eliana Marisa [UNESP]; Cavalcanti, Ismar Lima; Módolo, Norma Sueli Pinheiro [UNESP]; Vane, Luiz Antonio [UNESP] (Sociedade Brasileira para o Desenvolvimento da Pesquisa em Cirurgia, 2014)
PURPOSE: To verify the effects of different catecholamines on volemic expansion and on the autonomic nervous system in rabbits that were subjected to hemorrhage. METHODS: Twenty four rabbits subjected to hemorrhage (with a 25% loss of blood volume) and were randomly divided into four experimental groups: 1) HEMO Group underwent replacement with their own blood in an equal volume; 2) SS Group underwent replacement with saline solution (SS) in a volume that corresponded to three times the removed blood volume; 3) ISP Group underwent replacement with SS and isoprenaline; 4) FNL Group underwent replacement with SS and phenylephrine. Spectral Analysis of the heart rate and heart rate variability were performed from the recorded data. Hematocrit was measured throughout the experiment. RESULTS: Replacement with SS and an α- or β-agonist did not produce differences in the intravascular retention compared to replacement with SS alone. An analysis of HRV showed that the FNL group maintained the LF/HF ratio better than ISP and SS. CONCLUSIONS: No difference in vascular retention when α- or β- agonists were added to SS during post-hemorrhagic recovery. The animals in the FNL group maintained the integrity of the autonomic response within normal physiological standards during hemorrhagic stress.
Keywords: Catecholamines; Adrenergic alpha-Agonists; adrenergic beta-Agonists; Blood Volume; Hemorrhage; Autonomic Nervous System; Rabbits